Lean Six Sigma for dummies - Morgan, John 1949- (John Wiley, 2012)
If you want to make your organization or team more productive, you have to change the way it thinks. Combining the leading improvement methods of Six Sigma and Lean, this winning technique drives performance to the next level. But the jargon-packed language and theory of Lean Six Sigma can be intimidating for both beginners and experienced users. Whether you want to manage a project more tightly or fine-tune existing systems and processes, Lean Six Sigma For Dummies gives you plain-English guidance to achieve your business goals.
Includes index. - Includes bibliographical references and index
Keywords: Industrial management -- Handbooks, manuals, etc; Gestion d'entreprise; Guides, manuels, etc; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Industrial management; handbooks; Handbooks and manuals; Guides et manuels; Handbook